Pengaruh Kepemimpinan dan Budaya Organisasi terhadap Kinerja Fasilitator pada Program Kota Tanpa Kumuh di Kota Lubuklinggau - Wendy Syahputra; Maresta Dora (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The relationship of these theories with the three variables under study in which a competent and good leadership owned by a leader can influence and guide the facilitator to improve performance in order to achieve the expected goals. The method used in this research is the Quantitative Method. The population in this study was all the Facilitators, the sample taken in this study was the taking of the entire population or a saturated sample of 42 people. The hypothesis can be said to be proven and tested its truth, so it can be concluded that the Leadership and Organizational Culture have a significant or partially significant effect on the performance of the Facilitators in the Office of the City without Slums Program. Furthermore, the existence of Organizational Culture which is given by the leader to the facilitator can have an impact on the working spirit of the facilitator on the work, so as to obtain the expected results. This has an impact or effect on improving the Facilitator's Performance. This result is proven by the hypothesis and research conducted by researchers in which all three variables get positive and significant results. Thus if Leadership and Organizational Culture are implemented effectively and efficiently, it can improve the Performance of Facilitators in the Slumless City Program Office. Keywords: Leadership, Organizational Culture, Performance Facilitator.